Shah Wali Allah al-Dihlawi: Pemikir di Masa Krisis dan Pengaruhnya Terhadap Gerakan Islam di India - Luthfi Hadi Aminuddin (Justicia Islamica, 2007)
This study aims to analyze the thoughts of Shah Wali Allah al-Dihlawi in the context of the socio-political crisis that plagued India during his time and its influence on the Islamic movement in the region. This study explores the ideas of Islamic reform that he offered, including the reconstruction of fiqh, Sufism, and Islamic political thought. The method used is library research with a descriptive-analytical approach to the works of Shah Wali Allah, such as Hujjatullah al-Baligha, as well as academic research discussing his influence. The results of the research show that Shah Wali Allah attempted to respond to social disintegration through a synthesis between Sunni teachings and Sufism, as well as calling for the reform of Islamic education and government. His thoughts inspired Islamic reform movements in India, including Darul Uloom Deoband and others. This study confirms that his thoughts remain relevant in contemporary Islamic discourse.